A new species of Isonychia Eaton, 1871 (Ephemeroptera: Isonychiidae) from Taishun, China based on morphological characteristics and COX1 gene - Huang, Dong-Dong; Shen, Chen-Yang; Huang, Gui-Ying; Ye, Lin-Yu; Wu, Hui-Yuan; Zhang, Shu-Sheng; Cheng, Hong-Yi (Zootaxa, 2024)
Isonychia taishunensis Huang, Shen, Zhang & Cheng sp. nov. is described based on larval samples from Taishun County, Zhejiang Province, China. The new species is distinguished from other species of Isonychia Eaton by the following characters: gill plates with spines apically, the color of abdominal tergum X, color pattern of abdominal terga I–IX, and color pattern of each gill plate. The genetic distance between the new species and other species of Isonychia is over 10% using the Kimura 2-parameter model. The phylogenetic relationship of I. taishunensis is close to the clade of I. japonica Ulmer and I. ussurica Bajkova. The morphological characters and molecular data (COX1, Kimura 2-parameter) support that this new species represents the ninth species of the genus Isonychia in China. The modified key to known larvae of the genus Isonychia is provided.